Sanai - A wild edible vegetable plant species of Jharkhand - Pan, T K; Singh, C B (Indian Horticulture, 2021)
There are several unexploited plant species available in nature. Many cultivated vegetable plant species which are important part of our daily diet have originated from wild. Crotalaria tetragona Roxb. ex Andr., commonly known as sanai under the family Fabaceae a wild edible vegetable plant species has been collected from Saranda forest, Jharkhand. The specimen is also noted fro m kitchen garden Patratu, Ranchi, Jharkhand owing to cultivation for nutritional purposes. Its flowers are eaten by Santhal (a tribe) as a delicious vegetable food item. It has good potential which can be exploited for vegetable purpose.